Hypoxia and its Modification in Bladder Cancer: Current and Future Perspectives. Issue 6 (June 2021) - Lodhi, T.; Song, Y.P.; West, C.; Hoskin, P.; Choudhury, A.
Abstract: Radiotherapy plays an essential role in the curative treatment of muscle-invasive bladder cancer (MIBC). Hypoxia affects the response to MIBC radiotherapy, limiting radiocurability. Likewise, hypoxia influences MIBC genetic instability and malignant progression being associated with metastatic disease and a worse prognosis. Hypoxia identification in MIBC enables treatment stratification and the promise of improved survival. The most promising methods are histopathological markers such as necrosis; biomarkers of protein expression such as HIF-1α, GLUT-1 and CAIX; microRNAs; and novel mRNA signatures. Although hypoxia modification can take different forms, the gold standard remains carbogen and nicotinamide, which improve local control rates in bladder preservation and absolute overall survival with no significant increase in late toxicity. This is an exciting time for evolving therapies such as bioreductive agents, novel oxygen delivery techniques, immunotherapy and poly (ADP-ribose) polymerase 1 (PARP) inhibitors, all in development and representing upcoming trends in MIBC hypoxia modification. Whatever the future holds for hypoxia-modified radiotherapy, there is no doubt of its importance in MIBC. mRNA signatures provide an ideal platform for the selection of those with hypoxic tumours but are yet to qualified and integrated into the clinic. Future interventional trials will require biomarker stratification to ensure optimal treatment response to improve outcomes for patients with MIBC.